Aspects of the ecology and behaviour of bottlenose dolphins (Tursiops truncatus) in Santa Monica Bay, California - Bearzi, Maddalena (J. Cetacean Res. Manage., 2023)
The occurrence, distribution, site fidelity, group size and behaviour of common bottlenose dolphins (Tursiops truncatus) were assessed during a photo-identification study conducted between 1997-2001 in Santa Monica Bay, California. Bottlenose dolphins occurred yearround in the bay and were encountered on 56.8% of all surveys (n, total surveys=211). This species was found in waters within 0.5km of shore in 80.0% of the sightings (n=157), but sometimes found in deeper waters further offshore (>0.5km). No correlations between anomalies in sea surface temperatures during the 1997-98 El Niño event and sighting frequencies were observed. Group sizes varied significantly between schools observed inshore and offshore in the bay, with the largest groups sighted offshore. A total of 290 dolphins were individually photo-identified based on long-term natural marks on their dorsal fins. Forty-four individuals (15.2%) were encountered in both inshore and offshore waters, showing no exclusive fidelity to inshore waters. The low resighting rates of known individuals provided little evidence of long-term year-round site fidelity for Santa Monica Bay, revealing a range greater than the chosen study area. Several individuals, however, were resighted over one or two year periods, generally during more than one season. This suggested that these dolphins were highly mobile within the inshore waters of the Southern California Bight but they also spent time foraging and feeding in Santa Monica Bay, probably due to the presence of submarine canyons within this area. The behavioural budget for this species showed a predominance of activities characterised by travel and dive-travel (69.0%) and feeding (5.0%), indicating a fairly high proportion of time devoted to searching for prey and feeding in the study area.